2006
DOI: 10.1007/s00114-006-0132-z
|View full text |Cite
|
Sign up to set email alerts
|

Iridodial: a powerful attractant for the green lacewing, Chrysopa septempunctata (Neuroptera: Chrysopidae)

Abstract: The lacewing Chrysopa septempunctata Wesmael is an important, common predator of several insects in China, Japan, Russia, and many parts of Europe. Our field trapping experiments in northeast China showed that males of this green lacewing are strongly attracted to the lacewing pheromone of Chrysopa oculata Say, (1R,2S,5R,8R)-iridodial. The induced plant volatile, methyl salicylate, was unattractive to C. septempunctata by itself at the concentration tested, but synergistic when combined with iridodial where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 20 publications
1
32
1
1
Order By: Relevance
“…Hooper et al (2002) deduced that the attractive effect could be caused by incidental structural similarity of aphid sex pheromones to (yet unknown) pheromones of these lacewing species. This hypothesis seems to be supported by reports on a maleproduced compound, (1R,2S,5R,8R)-iridodial, identified from some Nearctic green lacewing species, which attracts males (Zhang et al 2004(Zhang et al , 2006a, and shows structural similarities to NEPOH and NEPONE. Additionally, catches by NEPOH and NEPONE are strongly male-biased (e.g., Boo et al 1999;Hooper et al 2002 and results of this study), again supporting the idea of NEPOH and NEPONE mimicking structurally related lacewing sex pheromones.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Hooper et al (2002) deduced that the attractive effect could be caused by incidental structural similarity of aphid sex pheromones to (yet unknown) pheromones of these lacewing species. This hypothesis seems to be supported by reports on a maleproduced compound, (1R,2S,5R,8R)-iridodial, identified from some Nearctic green lacewing species, which attracts males (Zhang et al 2004(Zhang et al , 2006a, and shows structural similarities to NEPOH and NEPONE. Additionally, catches by NEPOH and NEPONE are strongly male-biased (e.g., Boo et al 1999;Hooper et al 2002 and results of this study), again supporting the idea of NEPOH and NEPONE mimicking structurally related lacewing sex pheromones.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies have reported on the attractive effect of aphid sex pheromone components (enantiomers of nepetalactol and nepetalactone) to green lacewings; e.g., Chrysopa, Peyerimhoffina and Nineta species (Boo et al 1998Hooper et al 2002;Koczor et al 2010;Weihrauch 2006;Zhang et al 2004Zhang et al , 2006aZhu et al 2005). Hence, from a practical point of view, the combination of aphid sex pheromone compounds and the ternary floral bait could yield benefits by attracting a wider range of predatory insects.…”
Section: Introductionmentioning
confidence: 97%
“…) han sido recolectadas con trampas McPhail utilizando como atrayentes cariofileno, L-triptófano, fenilacetaldehído, iridodial o fosfato amónico+bórax, etc. (Hagen et al, 1976;Canard & Laudého, 1977Canard et al, 1979;Flint et al, 1979;McEwen et al, 1993aBakthavatsalam & Singh, 1996;Ahn et al, 2001;Tóth et al, 2006Tóth et al, , 2009Zhang et al, 2006b;Monserrat, 2008, etc. ) …”
Section: Datos Generales Sobre Su Biología Comportamiento Estadios unclassified
“…Lactol 16 and iridodial ( 17 ) have first been identified as defense compounds of ants [25]. More recently, 17 – which shows ( R )-configuration at C1 of the side-chain – was found to be a male-produced aggregation pheromone of lacewings [2627]. …”
Section: Resultsmentioning
confidence: 99%